Visuomotor reaction time and dynamic balance in children with cystic fibrosis and non‐cystic fibrosis bronchiectasis: A case‐control study. Issue 9 (22nd June 2020) - Dik, Jan; Saglam, Melda; Tekerlek, Haluk; Vardar‐Yagli, Naciye; Calik‐Kutukcu, Ebru; Inal‐Ince, Deniz; Arikan, Hulya; Eryilmaz‐Polat, Sanem; Dogru, Deniz
Abstract: Objective: Extrapulmonary involvement such as balance and reaction time is unclear in cystic fibrosis (CF) patients. The aim of this study was to evaluate visuomotor reaction time (VMRT) and dynamic balance in children with CF and non‐CF bronchiectasis compared to healthy children. Design/Methods: Demographic and clinical characteristics were recorded. All children were evaluated with pulmonary function test (PFT) using a spirometer, incremental shuttle walk test (ISWT) for exercise capacity, Fitlight Trainer for VMRT, and functional reach test (FRT) for dynamic balance. Results: Fourteen children with CF (10.71 ± 2.94 years, 7 females), 17 children with non‐CF bronchiectasis (12.75 ± 2.81 years, 8 females), and 21 healthy children (11.36 ± 3.28 years, 11 females) were included. Children with CF had longer total VMRT ( P  = .027), poorer FRT performance ( P  = .001), and shorter ISWT distances ( P  = .03) compared to the children with non‐CF bronchiectasis and controls. Although total VMRT was longest in the CF group, there was no significant difference in mean VMRT among the CF, non‐CF bronchiectasis, and control groups ( P  > .05). Conclusion: Dynamic balance and VMRT show greater impairment in children with CF than in children with non‐CF bronchiectasis compared to healthy controls. Our findings suggest that VMRT and dynamic balance should be taken into consideration for assessments and exercise programs in pulmonary rehabilitation.